The Effect of Intermittent Fasting on Glucose and Lipid Disorder among patients of Diabetes Mellitus Type-2 - Sajjad Khan, Irfan Rafiq Bhatti, Ghulam S. Jarwar, Sumaira Naeem, Javed Iqbal, Samreen Rizwan, Muhammad Yahya, Saadia Sajjad (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The diabetes Mellitus Type -2 disease has become prevalent globally and the treatment of the disease is quite expansive and long term, especially in the low-income countries like Pakistan. Aim: To explore the evidence of the efficacy of Intermittent Fasting as an alternative therapy in Diabetes Mellitus Type-2 by reviewing the existing literature on intermittent fasting globally. Methods: The literature on the effect of Intermittent Fasting on diabetes type-2 was searched on PubMed, and Google scholar and more than 20 studies conducted on the IF on human beings were identified at national, regional, and global levels and reviewed. Results: Not much literature is available on Intermittent Fasting, especially in low-income countries and the majority of the studies have been conducted in high-income countries like the USA, Canada, Australia, and the UK. A few long-term, Randomized Control Trials have been conducted, and most are short-term studies. A few studies have been found on Diabetes Mellitus Type-2 in India and Pakistan that too related to the prevalence and economic burden of the disease in these countries. Conclusion: Based on the studies reviewed, we can conclude that there is growing evidence demonstrating the benefits of Intermittent Fasting in short- and medium-term studies on glucose and lipid homeostasis but there is a need to carry out more long-term studies with a larger number of participants and in low-income countries. Furthermore, the existing literature reveals that Intermittent Fasting can be used as an alternative in the supervision of physicians otherwise can be counterproductive.